Emotional Intelligence, Resilience, and Engagement in Post-COVID-19 Pandemic Learning for College Students - Ar'ruumazakia Paramadina Mulia; Alldila Nadhira Ayu Setyaning (PT SOLUSI EDUKASI BERDIKARI, 2024)
This study aims to show how students’ emotional intelligence affects their resilience, with an impact on engagement and subsequent academic performance. This research was conducted quantitatively and used questionnaires as the data collection method. This study used partial leasts squares structural equation modeling (PLS-SEM) method with SmartPLS v4.0 analysis tool. The population of this study were all students from various universities in Yogyakarta and the sample used was 212 students in Yogyakarta. The results showed that: emotional perception, emotional use, emotional understanding, and social emotional management did not affect resilience. Then on individual emotional management affects resilience, resilience affects engagement, and engagement affects academic performance.